2014
DOI: 10.1016/j.jpeds.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Parent Health Literacy and “Obesogenic” Feeding and Physical Activity-Related Infant Care Behaviors

Abstract: Objective To examine the relationship between parent health literacy and “obesogenic” infant care behaviors. Study design Cross-sectional analysis of baseline data from a cluster randomized controlled trial of a primary care-based, early childhood obesity prevention program (Greenlight). English and Spanish-speaking parents of 2 month old children enrolled (n=844). The primary predictor variable was a parent health literacy (Short Test of Functional Health Literacy in Adults (STOFHLA); adequate>=23; low<23).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
59
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 27 publications
8
59
1
1
Order By: Relevance
“…Our findings are largely consistent with previous studies showing associations of low parent health literacy with pediatric 9,[11][12][13][14][15][16][17]32 and adult 3 health outcomes. Similar to a clinic-based study by Heerman et al, 12 parents with low health literacy in our sample were less likely than parents with adequate health literacy to adhere to certain injury prevention practices, such as having their hot water heaters set to <120°F or ensuring the home had a working smoke detector.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are largely consistent with previous studies showing associations of low parent health literacy with pediatric 9,[11][12][13][14][15][16][17]32 and adult 3 health outcomes. Similar to a clinic-based study by Heerman et al, 12 parents with low health literacy in our sample were less likely than parents with adequate health literacy to adhere to certain injury prevention practices, such as having their hot water heaters set to <120°F or ensuring the home had a working smoke detector.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to a clinic-based study by Heerman et al, 12 parents with low health literacy in our sample were less likely than parents with adequate health literacy to adhere to certain injury prevention practices, such as having their hot water heaters set to <120°F or ensuring the home had a working smoke detector. Consistent with Yin et al, 11 we also found that parents 5 by guest on May 9, 2018 http://pediatrics.aappublications.org/ Downloaded from with low health literacy were more likely to report television watching of >2 hours per day by their children, an obesogenic risk factor in preschool and young adult populations. 33 In contrast to other studies, however, parents with low health literacy were not more likely to report improper car seat placement, 12 and unexpectedly, they were also less likely to report having a television in the child's bedroom.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Obesity in infants is a controversial topic; however, research supports a link between rapid early infant growth and later obesity. [60][61][62][63] Feeding. There are concerns with diagnosing obesity in infancy because of the unintended consequence of a mother's restricting food intake during infancy; restriction of fat intake can adversely impact brain development.…”
Section: Obesity Prevention Measures In Early Lifementioning
confidence: 99%
“…85 Parental health literacy effects can create an obesogenic infant feeding environment; parents with low health literacy were significantly more likely to formula feed their children, feed as soon as the infant cried, and force the infant to consume all the bottle and early solid food supplement. 62 Since health literacy can be increased by education, a childhood obesity prevention strategy might be to increase parent's health literacy so that they do not create obesogenic conditions for their child. Higher caloric consumption (ie carbohydrate) during solid food supplementation is associated with higher BMI in childhood.…”
Section: Obesity Prevention Measures In Early Lifementioning
confidence: 99%